Problem Solving and Cooperative Learning Model of the Jigsaw Type: IPAS Learning Outcomes in Elementary School - Supiarti, Supiarti; Selvi, Nurhayati; Fajrin, Syarifah Nur (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The low learning outcomes of Natural and Social Sciences (IPAS) in elementary schools are the main challenge in this study. This study aims to test and compare the effectiveness of the problem-solving learning model and the jigsaw cooperative learning model in improving the learning outcomes of fourth-grade students in Elementary School Inpres Tello Baru 1I in the 2025/2026 academic year. The research method used is a quantitative approach with a quasi-experimental design (Non-Equivalent Control Group Design) involving 54 students. Data was collected through observation sheets of teacher and student activities and learning outcome tests. The findings indicated that both models significantly improved the quality of teacher instruction and active student participation. Teachers achieved a score of 93.33% in the problem-solving model and a perfect score of 100% in the jigsaw model at the fourth meeting. Student activity also increased drastically, reaching 92.30% in the problem-solving model and 100% in the jigsaw model. Statistically, there is a significant difference in learning outcomes between the experimental and control classes, where the average posttest score of the experimental class (83.93) is much higher than the control class (73.08). The t-test produces a calculated t value (3.004) > t table (2.006), which proves that the use of the problem-solving and jigsaw models has a greater positive impact than the conventional method. This study recommends both models as innovative strategies to address the low learning outcomes of IPAS in elementary schools.